Detection of monoclonal antibodies using chemically modified graphite substrates - Zari Tehrani (2010 IEEE Sensors, 2010)
This paper presents a novel sensor device based on chemically modified Highly Ordered Pyrolytic Graphite (HOPG). Biosensor diagnostics based on bio-functionalised semiconductor devices are an important development in ultrasensitive sensors for early detection of disease biomarkers. Electrochemical devices using chemically modified graphite (CMG) channels are excellent candidates for nano-biosensors [1]. By attaching aniline to HOPG, via coupling with an aryl diazonium salt, the amino group of the aniline molecule has been used to graft antibodies - (1) targeted against beta-actin and (2) targeted against 8-hydroxydeoxyguanosine (8-OHdG) - onto the HOPG surface. Antibody attachment to graphitic surfaces has been verified using Laser Scanning Confocal Microscopy (LSCM) to detect attached quantum-dot labeled antibodies. Furthermore, the current-voltage characteristics of virgin and chemically modified HOPG surfaces have been used to detect the presence of antibodies at nM concentrations.